The Sweet Taste of Adapting to the Desert: Fructan Metabolism in Agave Species - Pérez-López, Arely V.; Simpson, June (Frontiers in Plant Science, 2020)
Over 70% of Agave species, (159 of 206) are found in Mexico and are well adapted to survive under hot, arid conditions, often in marginal terrain, due to a unique combination of morphological and physiological attributes. In the pre-Columbian era agaves were also key to human adaptation to desert terrain since nomadic tribes depended on these plants as sources of food, fiber and construction materials. In contrast to other species such as cacti or resurrection plants, Agaves store carbohydrates in the form of fructan polymers rather than starch or sucrose, however properties specific to fructans such as a strong hydration shell, the ability to be transported through phloem, variable composition throughout the agave life-cycle and accumulation in succulent tissues and flowers suggest a potential for multiple functional roles. This mini-review summarizes current knowledge of molecular and biochemical aspects of fructan metabolism in Agave species.